Mesoscale patterns in the Cape Sao Vicente (Iberian Peninsula) upwelling region - Relvas, Paulo (2018)
The coastal upwelling region near Cape Sao Vicente, the southwestern tip of the Iberian Peninsula where the southern zonal coast meets the meridional western coast, was studied using over 1200 advanced very high resolution radiometer (AVHRR) satellite images of sea surface temperature and time series of sea level height, wind velocities, and nearshore sea surface temperature recorded at coastal sites within 200 km of the cape. Summer upwelling is more intense and persistent off the western coast than off the southern coast, where a recurrent warm coastal countercurrent flows westward, and at times turns northward along the western coast after reaching the cape. In this region the equatorward current jet of cold water upwelled off the western coast is no longer bounded by a coast. Three preferred directions for the spreading of this water are identified. The most persistent is eastward along the southern shelf break and slope, possibly merging with waters previously upwelled locally, which becomes separated from shore by the coastal progression of the warmer counterflow. The second preferred direction results in the southward development of a cold filament feature fed by cold waters upwelled farther north and represents the southernmost extent of the intense coastal upwelling jet, which overshoots the cape. The least frequent feature to develop is a cold filament that grows westward at the latitude of the cape, appearing to result from the meandering of the equatorward jet. The coastal countercurrent is seen to interact with the equatorward jet at times of relaxation, not only by separating the cold upwelled water from the coast but, when it is energetic enough, breaking westward offshore through the equatorward cold flow and separating the eastward and southward cold features from the upcoast cold waters. Empirical evidence shows the presence of an alongshore pressure gradient, stronger in summer, driving the coastal progression of the warm counterflow. Wind forcing plays an important role in the circulation by augmenting or diminishing the effect of the preexisting alongshore pressure gradients. The extent of the progression of the warm coastal countercurrent along the southern and western coast is dictated by the the strength of the upwelling favorable wind stress, which is able to balance and reverse the alongshore flow, at least in the upper layers.